2023
DOI: 10.1111/jan.15602
|View full text |Cite
|
Sign up to set email alerts
|

Registered nurse mentors' experiences from co‐creation in higher education targeting enhancement of mentorship practices in nursing homes: A qualitative study

Abstract: Aim To explore registered nurse (RN) mentors' experiences of participating in the co‐creation of a digital educational resource intended to enhance mentorship practices of first‐year nursing students in clinical placement in nursing homes. Design An interpretive, descriptive qualitative study design. Methods Data were collected through two focus group interviews with 15 RN mentors (n = 15) participating in co‐creative workshops. The co‐creative process entailed four co‐creative workshops conducted over a 17‐mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The pilot study aimed to evaluate the educational resource (DigiViS) and inform the final development of the full‐scale interactive digital educational resource targeting all stakeholder groups (student nurses, nurse educators and registered nurse mentors) and quality dimensions (supervision and assessment competencies, student nurses' reflective thinking skills and learning experience, tripartite communication and collaboration). The pilot study and evaluation have been documented and reported elsewhere (Frøiland et al, in review; Laugaland et al, in review).…”
Section: Results: the Co‐creative Processmentioning
confidence: 99%
See 3 more Smart Citations
“…The pilot study aimed to evaluate the educational resource (DigiViS) and inform the final development of the full‐scale interactive digital educational resource targeting all stakeholder groups (student nurses, nurse educators and registered nurse mentors) and quality dimensions (supervision and assessment competencies, student nurses' reflective thinking skills and learning experience, tripartite communication and collaboration). The pilot study and evaluation have been documented and reported elsewhere (Frøiland et al, in review; Laugaland et al, in review).…”
Section: Results: the Co‐creative Processmentioning
confidence: 99%
“…This is surprising because 50% (90 ECTS) of bachelor nursing programmes involve clinical placements. The inclusion and active engagement of registered nurse mentors with diverse backgrounds allowed new perspectives and essential insights to emerge in the co-creative process, representing critical perspectives informing educational initiatives (Frøiland et al, 2023). Previous studies have emphasized the need to strengthen collaborations between academic educators and registered nurses in clinical settings to learn from each other's practice, reduce theory-practice divides and decrease the hierarchical separation between academic educators and clinical practitioners (Dev et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…nursing students and nurse educators) to ensure a resource in better alignment with the needs and perspectives of RN mentors [ 30 ]. The co-creative developmental process has been previously detailed by [ 23 ] and [ 31 ]. The DER was designed to support and enhance the mentorship practices for first-year nursing students during clinical education in nursing homes.…”
Section: Methodsmentioning
confidence: 99%